2017
DOI: 10.1021/acsnano.6b05982
|View full text |Cite
|
Sign up to set email alerts
|

Spin–Orbit Coupling Induced Gap in Graphene on Pt(111) with Intercalated Pb Monolayer

Abstract: Graphene is one of the most promising materials for nanoelectronics owing to its unique Dirac cone-like dispersion of the electronic state and high mobility of the charge carriers. However, to facilitate the implementation of the graphene-based devices, an essential change of its electronic structure, a creation of the band gap should controllably be done. Brought about by two fundamentally different mechanisms, a sublattice symmetry breaking or an induced strong spin-orbit interaction, the band gap appearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
110
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 38 publications
5
110
0
Order By: Relevance
“…5c). This is the first time that the band dispersion in the valence band of graphene patches orientated with the main directions of the Pt(111) crystal has been measured, instead of the ARPES more usually reported, which pertains to the superstructure rotated by 30° [44,51,52,53] The full wave-vector ARPES data clearly prove the presence of graphene oriented with h-BN on a large scale, which occurs due to a 2D heteroepitaxial growth favoured by the h-BN edges [25,54].…”
Section: Resultsmentioning
confidence: 74%
“…5c). This is the first time that the band dispersion in the valence band of graphene patches orientated with the main directions of the Pt(111) crystal has been measured, instead of the ARPES more usually reported, which pertains to the superstructure rotated by 30° [44,51,52,53] The full wave-vector ARPES data clearly prove the presence of graphene oriented with h-BN on a large scale, which occurs due to a 2D heteroepitaxial growth favoured by the h-BN edges [25,54].…”
Section: Resultsmentioning
confidence: 74%
“…The first case should induce changes mainly in the G's properties already perturbed by the metal surface, while the latter might significantly alter the graphene-substrate proximity, as graphene will now interact with the metal mainly via the intercalated adatom. Importantly, both decoration and intercalation can be realized experimentally [12][13][14][15][16][17][18][19][20][21][22][23] and are known to provide several interesting options for engineering of graphene's properties, in addition to any possible enhancement of SOC [24]. Here, we will focus on two previously studied models, G/Pt(111) and G/Au/Ni(111) which present markedly different electronic and magnetic properties, and consider the adsorption of one species for each system, namely, a Pt adatom for G/Pt(111) and an Au adatom for G/Au/Ni(111).…”
Section: Introductionmentioning
confidence: 99%
“…It has even been shown that the stepwise intercalation of silicon and oxygen can lead to silicon oxide formation under epitaxial graphene, electrically isolating the graphene from the highly conductive substrate on which it is grown [27], and re-establishing the innate properties of the graphene. Further effects of intercalation can be the generation of substantial electron or hole doping densities [24,[28][29][30], an increase in the intrinsically very weak spin-orbit interaction [31,32] and the induction of superconductivity [33]. Given this ability to bestow graphene with new properties and to suppress the graphene-substrate interaction by intercalation, it is tempting to assume that epitaxially grown SL TMDCs could equally profit from such an approach.…”
mentioning
confidence: 99%